Democracy in motion evaluating the practice and impact of deliberative civic engagement - Nabatchi, Tina. (Oxford : Oxford University Press, 2013)
This title uses theory, research, and practice to comprehensively explore what we know, how we know it, and what remains to be understood about deliberative civic engagement. The book is useful to scholars, practitioners, public officials activists, and citizens who seek to utilize deliberative civic engagement in their communities.
Includes bibliographical references and index.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Political participation; Deliberative democracy; Decision making -- Citizen participation; Political planning -- Citizen participation